Microbiome profiling reveals gut bacterial species associated with rapid lung function decline in people with HIV - Bai, Xiangning; Raju, Sajan C.; Knudsen, Andreas Dehlbæk; Thudium, Rebekka Faber; Arentoft, Nicoline Stender; Gelpi, Marco; Heidari, Safura-Luise; Kunisaki, Ken M.; Kristiansen, Karsten; Hov, Johannes Roksund; Nielsen, Susanne Dam; Trøseid, Marius (Frontiers in Immunology, 2025)
BackgroundPeople with HIV (PWH) have an increased risk of pulmonary comorbidities compared to people without HIV. The gut microbiome regulates host immunity and is altered in PWH. This study aims to determine potential associations between gut microbiome, lung function decline, and airflow limitation in PWH.MethodsPWH from the Copenhagen Comorbidity in HIV Infection (COCOMO) Study with available lung function testing and microbiome data were included (n=385). The gut microbiome was characterized using shotgun metagenomic sequencing. Associations between gut microbiome, rapid lung function decline, and airflow limitation were analysed in multivariable logistic regressions adjusted for traditional and HIV-associated risk factors for lung disease.ResultsSeveral bacterial species were significantly enriched in PWH with rapid lung function decline, including opportunistic pathogenic bacterial species Bacteroides coprophilus, Klebsiella michiganensis, and Clostridium perfringens. A gut microbial dysbiosis index based on compositional changes was associated with rapid lung function decline (adjusted odds ratio (aOR) 1.18, 95% confidence interval (CI) [1.11-1.27], p<0.001), and airflow limitation (aOR 1.16, 95% CI [1.04-1.29], p=0.007) in adjusted multivariable logistic regression analyses.ConclusionAssociations between the gut dysbiosis index and rapid lung function decline and airflow limitation suggest a potential role of certain gut bacterial species in the pathogenesis of pulmonary comorbidities in PWH.